Methodological challenges in the transition towards online audience research - Mathieu, David (2016)
This review of the literature published between 2005 and 2014 presents an overview of the methodological environment in which audience research is transiting towards the study of online audiences. Online audience research is a mix of long-established research rationales, methodical adaptations, new venues and convergent thinking. We discuss four interconnected, and sometimes contradictory, methodological trends that characterize this current environment: 1) the expansion of online ethnography and the continued importance of contextualization, 2) the influence of big data and an emphasis on uses, 3) the reliance on mixed methods and the convergence of different rationales of research, and 4) the ambiguous nature of online data and the ethical considerations for the conduct of research. In spite of a massive research activity, there remain gaps and underprivileged areas that call for a re-prioritization of research. In the conclusion of this paper, we offer recommendations to orient future research.